Penerapan Pembagian Bagian Anak Perempuan Pasal 176 Kompilasi Hukum Islam (KHI) - Syuhada' Syuhada' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Abstract: The Science of Far'idh is discussing or regulating various matters in the distribution of inheritance to those entitled to receive it from the basic provisions stipulated in the Koran, the sunnah of the Holy Prophet. and ulam agreement '. The object is the distribution of inheritance for heirs who are entitled to receive. The benefit of this knowledge is that it can provide heir rights to inheritance (HP) in accordance with Islamic Sharia guidance based on the Qur'an, Al-Hadit, Al-'Ijmâ ‘and Al-Qiyâs. KHI article 176 "If only one part of a daughter gets a share, if two or more people jointly get two parts, and get a daughter together with a boy, so the share of a boy is two to one with daughters. "The part of girls in article 176 KHI receives a separate part with the requirements and bodies that are not accepted by boys. When leaving a son joins, the girl gets one part and the boy gets two parts The share of girls in article 176 KHI receives a third part of the requirements of two or more people and the body does not accept boys When leaving a son joins, the girl gets one part and the boy gets two parts. girls in article 176 KHI join boys and girls get one part while boys get two parts.